Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/lary.29404
|View full text |Cite
|
Sign up to set email alerts
|

The Risks of Complications During Endoscopic Sinus Surgery in Cystic Fibrosis Patients: An Anatomical and Endoscopic Study

Abstract: Objective/Hypothesis An increasing proportion of adult cystic fibrosis (CF) patients is being referred to endoscopic sinus surgery (ESS) in order to relieve the symptoms of chronic rhinosinusitis (CRS). Given that CFTR mutations profoundly alter sinonasal development, we want to explore the relationship between their peculiar surgical anatomy and the risk of postoperative complications. Study Design Retrospective case‐control study. Methods Paranasal sinuses CT scans of 103 CF adult patients with CRS were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
0
4
0
2
Order By: Relevance
“…However, on multivariate analysis, only severe postoperative pain (score ≥7/10) was associated with the need for overnight admission 82 . Maggiore et al found significant anatomic differences between CF and non‐CF patients, but no significant increase in surgical complication rate associated with ESS 83 . Spielman et al demonstrated the feasibility of avoiding general anesthesia and performing revision in‐office ESS in patients with CF CRS 84 …”
Section: Resultsmentioning
confidence: 99%
“…However, on multivariate analysis, only severe postoperative pain (score ≥7/10) was associated with the need for overnight admission 82 . Maggiore et al found significant anatomic differences between CF and non‐CF patients, but no significant increase in surgical complication rate associated with ESS 83 . Spielman et al demonstrated the feasibility of avoiding general anesthesia and performing revision in‐office ESS in patients with CF CRS 84 …”
Section: Resultsmentioning
confidence: 99%
“…The depth of the olfactory fossa is interpreted here as an expression of pneumatization of the frontal recess. Although CF patients underwent more extensive surgery on average than non-CF patients, there was no increased rate of complications such as olfactory fossa injury with CSF or orbital complications due to injury of the lamina papyracea [146].…”
Section: Surgical Remediation Of Cf-crsmentioning
confidence: 94%
“…Die Autoren erklären diesen Tatbestand dadurch, dass die Ausreifung der Nebenhöhlenbelüftung im Jugendalter auch abhängig ist von einer kontinuierlichen Luftzufuhr des Bereichs und im CF Kollektiv somit die Ausdehnung der lufthaltigen Räume im Mittelgesicht im Vergleich vermindert ist. Die Tiefe der Riechrinne wird hierbei als Ausdruck einer Pneumatisation des Recessus frontalis interpretiert.Obwohl die CF-Patienten im Schnitt ausgiebiger operiert wurden als die Nicht-CF-Patienten, kam es zu keiner erhöhten Rate an Komplikationen wie einer Riechrinnenverletzung mit Liquorrhoe oder orbitaler Komplikationen durch Verletzungen der Lamina papyracea[146].Im Rahmen einer deutschen Studie wurde ein MRT-Screening bei 67 Vorschulkindern mit CF durchgeführt, um die Entwicklung der Nasennebenhöhlen und die Prävalenz von krankheitsspezifischen Veränderungen im Vergleich zu einer an den Nebenhöhlen gesunden Kontrollgruppe von 30 Kindern zu untersuchen. In der CF-Gruppe waren die Kinder 2,3 Jahre alt, in der Kontrollgruppe 3,5 Jahre.…”
unclassified
“…Endoscopic sinus surgery (ESS) is generally accepted as the standard of care for patients with sinonasal disease who have failed adequate medical treatment. 1 Despite the safety and efficacy associated with ESS, major complications are reported in 0.5% to 1.0% of ESS cases. 2 Such complications include injury to critical vascular structures, injury to the skull base, and injury to the orbit.…”
Section: Introductionmentioning
confidence: 99%